Parâmetros radiográficos de displasia coxofemoral na raça Rottweiler - Paula Cristina Genuino (2010)
The aim of this study was to evaluate the parameters Norberg angle, femoral cortical index, percentage of coverage of the femoral head by the acetabulum and femoral angle of inclination based on gender and age of animals correlated with the incidence and severity of hip dysplasia . We evaluated 139 radiographs, 44 dogs from males and 95 females. Radiographs were classified by the degree of hip dysplasia, and we measured the angle of inclination, Norberg angle, the cortical index and percentage of coverage of the femoral head on both sides. The mean frequency of DCF in this study in Rottweiler was 70.51%, being very high. In dysplastic animals the mean Norberg angle was 100.09 ± 7.86 °, the mean percent coverage of the femoral head was 41.50 ± 8.59%, the mean femoral cortical index was 0.33 ± 0 , 04, and femoral angle mean was 153.06 ± 9.81 °. Higher inclination angles were associated with smaller angles of Norberg and lowest percentage of coverage of the femoral head. It was observed that with increasing age, the animals had lower angles Norberg, lower percentage of coverage of the femoral head and greater degree of dysplasia. In this study gender, cortical index and angle of inclination did not show any association with the DCF.